2019
DOI: 10.1038/s41598-019-53447-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the interaction between human choline kinase alpha and the SH3 domain of the c-Src tyrosine kinase

Abstract: Choline kinase alpha is a 457-residue protein that catalyzes the reaction between ATP and choline to yield ADP and phosphocholine. This metabolic action has been well studied because of choline kinase’s link to cancer malignancy and poor patient prognosis. As the myriad of x-ray crystal structures available for this enzyme show, chemotherapeutic drug design has centered on stopping the catalytic activity of choline kinase and reducing the downstream metabolites it produces. Furthermore, these crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…Kall et al have also very recently demonstrated, through SPR and crystallographic analysis, that ChoKα interacts with cSrc by a non-catalytic poly-proline motif (residues 60-69; see PDB ID: 6C4S) located in hChoKα N-terminal domain. 83 This finding could lead to the design of new inhibitors that disrupt this hChoKα-cSrc interaction.…”
Section: High-throughput Screening Of Compound Collectionmentioning
confidence: 99%
“…Kall et al have also very recently demonstrated, through SPR and crystallographic analysis, that ChoKα interacts with cSrc by a non-catalytic poly-proline motif (residues 60-69; see PDB ID: 6C4S) located in hChoKα N-terminal domain. 83 This finding could lead to the design of new inhibitors that disrupt this hChoKα-cSrc interaction.…”
Section: High-throughput Screening Of Compound Collectionmentioning
confidence: 99%
“…ChoKα catalyzes the phosphorylation of choline to phosphocholine, and its high expression has proven to be associated with cancer malignancy and poor patient prognosis ( Ramírez De Molina et al , 2002 , 2005 ). Recent biophysical and biochemical studies ( Kall et al , 2019 ) have demonstrated that the ChoKα poly-proline region in residues 49–79 (especially prolines 61 and 62) mediates the physical interaction between ChoKα and the SH3 domain of c-Src tyrosine kinases. It can be seen in the ChoKα importance map ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…( b ) Analysis of the potential importance of each residue in ChoKα for interaction with the SH3 domain of c-Src. The poly-proline region in ChoKα residues 53–78 harbors relatively higher scores in the importance map , which are reported crucial for the interaction with the SH3 domain of c-Src ( Kall et al , 2019 )…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of ChoKα seems to correlate with a higher cell proliferation rate. Recently, this interaction has been mapped at the SH3 domain of c-Src and the poly-proline region N-terminal of ChoKα [99]. The relationship of ChoKα and EGFR, has also been reported in lung [100] and liver tumors [35] and has been associated with resistance to EGFR inhibitors [35].…”
Section: Choks More Than Metabolism Enzymes?mentioning
confidence: 93%